2017
DOI: 10.1086/694447
|View full text |Cite
|
Sign up to set email alerts
|

On the Pleistocene Population History in the Japanese Archipelago

Abstract: This paper provides a current understanding of human population history in the Pleistocene Japanese Archipelago, particularly with respect to the routes and timing of hunter-gatherer migrations, by incorporating multiple lines of evidence from the records of archaeology, human paleontology, and genetic studies. The human fossil remains are concentrated on the Ryukyu Islands in southwestern Japan, suggesting that there may have been a northward migration via the Ryukyu Islands. In contrast, studies of ancient m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…It is possible there was some clinal variation within the macaques which survived the last glaciation in mid-to-South Japan, potentially giving the northernmost survivors a ‘head-start’ on adapting to higher latitudes following climatic amelioration, although this is not visible from the molecular data 54 . Although the earliest Jomon sites date to ~15,000 BP 29 , the oldest human remains in Japan are dated to ~30,000 BP 55 . There is debate over the extent of continuity between the Neolithic Jomon and the preceding Palaeolithic population(s) of Japan 55 , but there are apparent morphological similarities between the Jomon and some of the earliest well-preserved Japanese inhabitants, dated to ~30-15,000 BP 56–58 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible there was some clinal variation within the macaques which survived the last glaciation in mid-to-South Japan, potentially giving the northernmost survivors a ‘head-start’ on adapting to higher latitudes following climatic amelioration, although this is not visible from the molecular data 54 . Although the earliest Jomon sites date to ~15,000 BP 29 , the oldest human remains in Japan are dated to ~30,000 BP 55 . There is debate over the extent of continuity between the Neolithic Jomon and the preceding Palaeolithic population(s) of Japan 55 , but there are apparent morphological similarities between the Jomon and some of the earliest well-preserved Japanese inhabitants, dated to ~30-15,000 BP 56–58 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the earliest Jomon sites date to ~15,000 BP 29 , the oldest human remains in Japan are dated to ~30,000 BP 55 . There is debate over the extent of continuity between the Neolithic Jomon and the preceding Palaeolithic population(s) of Japan 55 , but there are apparent morphological similarities between the Jomon and some of the earliest well-preserved Japanese inhabitants, dated to ~30-15,000 BP 56–58 . The Jomon therefore, can be said to have at least some input from populations with a history in Japan dating back to ~30,000 BP.…”
Section: Discussionmentioning
confidence: 99%
“…A major colonization event that has not received as much attention is the peopling of the Japanese archipelago; it has been suggested that this could have occurred during MIS 6, when a land connection was likely present, or some time during MIS 3, when no land connection existed (28,(65)(66)(67). Given that only a few sites in Japan predate 40 ka, and that there are questions about the context and/or artifactual nature of the materials at those localities, the earliest presence of modern humans in Japan is considered to be about 40 ka (67). Assuming that this date is correct, the initial colonization would have had to involve some type of watercraft and a high degree of seafaring skill (28,34,65,66).…”
Section: Fads and Taqsmentioning
confidence: 99%
“…A third underlying theme among the archaeology-centered papers is the role of so-called modern human behaviors in successful and unsuccessful dispersals by modern Homo sapiens across Asia. In particular, it is fairly clear that a set of novel behaviors accompanied, and perhaps facilitated, colonizations of regions like the Japanese archipelago and island Southeast Asia (Bae 2017;Nakazawa 2017;O'Connor et al 2017). Some of these behaviors may have included different functional uses of ground stone tools like axes and the independent development of equipment for fishing.…”
Section: Laying the Foundation: Contributions From Archaeologymentioning
confidence: 99%